The epidemiology of burns in children in Guatemala: a single center report - Santiso, Lourdes; Tapking, Christian; Lee, Jong O; Zapata-Sirvent, Ramon; Pittelli, Christine A; Suman, Oscar E. (Journal of burn care & research, 2020)
Children in low- to middle-income countries are at high risk for sustaining severe burns. This study aimed to analyze the characteristics of pediatric burns in Guatemala that could help identify risk factors and guide prevention efforts. A retrospective review of the characteristics of patients < 18 years of age that were burned in Guatemala between 2015 and 2018 and treated at the Hospital Roosevelt Burn Unit in Guatemala City was performed. The medical records of 949 patients were reviewed (year 2015: 224, year 2016: 238, year 2017: 251, year 2018: 236). Mean age of the patients was 4.0 ± 3.6 years. Majority of the patients were male (54.2%) and suffered from scald burns (68.5%) due to spilling or falling into hot water. Children under the age of 9 years predominantly suffered from scald burns, whereas older children more frequently sustained flame burns. The mortality rate over the 4-year period was 5.2%. As in other low-income countries, pediatric burns in Guatemala are frequent and usually due to scald. Demographic characteristics have to be taken into account when developing strategies for improvements of prevention and treatment or transferring these from high-income countries. Especially education of parents and safety of daily tasks are crucial. Special attention and focusing of efforts in areas of higher incidence should be sought.
Published 26 August 2019
Gesehen am 11.01.2021